2014
DOI: 10.1007/s10195-014-0288-9
|View full text |Cite
|
Sign up to set email alerts
|

Carpometacarpal dislocation of the thumb associated with fracture of the trapezium

Abstract: Carpometacarpal dislocation (CMC) of the thumb associated with fracture of trapezium is an extremely rare injury, with only 12 cases that sustained similar injuries reported in the literature. In this article, another patient with this rare injury was reported, and all previously published cases were extensively reviewed. The presented case and all previously published cases had a longitudinally oriented trapezium fracture, which is naturally unstable and almost always associated with dislocation of the CMC jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…Ramoutar et al [ 3 ] indicated a direct dorsoradial impaction or indirect axial loading as mechanisms for the injury, which is consistent with case 1 in the current study. Kose et al [ 4 ] reported either axial loading on a flexed thumb or commissural shearing forces acting on the first web space as the mechanism of injury, most likely consistent with the mechanism of the injury for cases 2 and 3 in the current study.…”
Section: Discussionsupporting
confidence: 79%
“…Ramoutar et al [ 3 ] indicated a direct dorsoradial impaction or indirect axial loading as mechanisms for the injury, which is consistent with case 1 in the current study. Kose et al [ 4 ] reported either axial loading on a flexed thumb or commissural shearing forces acting on the first web space as the mechanism of injury, most likely consistent with the mechanism of the injury for cases 2 and 3 in the current study.…”
Section: Discussionsupporting
confidence: 79%
“…In most cases, a trapezium fracture also accompanies other injuries such as Rolando's fracture, Bennett's fracture dislocation, scaphoid fracture, and usually dislocation of the first CMC joint. 4,8 The trapezium articulates with four bones: the first metacarpal distally, the scaphoid proximally, and with the trapezoid and second metacarpal medially (►Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…20 There are two main injury mechanisms for thumb CMC dislocations and trapezium fractures. 4,5 The mechanism of injury usually involves either indirect axial overload or direct dorsoradial impaction. 3 An indirect axial overload caused by a fall on the out-stretched hand, resulting in hyperextension and radial deviation of the hand, where the trapezium gets compressed between the base of the first metacarpal and the radial styloid, resulting in a shear fracture through the radial side of the body of the trapezium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations